Editorial (Journal of Forest and Livelihood, 2004)
It is a great pleasure for us to present the fifth issue of the ‘Journal of Forest and Livelihood’. The journal seeks to document and disseminate emerging insights, lessons and innovations taking place in various dimensions of forestry and rural livelihoods in Nepal. In this issue, we have included eight articles, which analyse policy and governance aspects of forest management and livelihoods of local communities who depend on forests. Forest user groups and their engagement with natural resources in the community forests have become a common ground to talk about questions, issues and experiences but with respective perspectives of authors mainly in the topical area called Community forestry ( CF ).